Weight Loss and Melatonin Reduce Obesity-Induced Oxidative Damage in Rat Testis - Dogan Atilgan; Bekir S. Parlaktas; Nihat Uluocak; Fikret Erdemir; Sahin Kilic; Unal Erkorkmaz; Huseyin Ozyurt; Fatma Markoc (Advances in Urology)
Aim. We aimed to evaluate the antioxidant effects of weight loss and melatonin on the obesity-induced oxidative damage in rat testes. Materials and Methods. 28 male Wistar albino rats were randomly divided into 4 groups, each consisting of 7 rats: control group (Group 1), obesity group (Group 2), obesity + MLT group (Group 3), and weight loss group (Group 4). Rats were weighed at the beginning and at the end of the study. Bilateral orchiectomy was performed and 5 cc blood samples were obtained from all of the rats. Superoxide dismutase (SOD), malondialdehyde (MDA), and protein carbonyl (PC) levels were analysed in the testicular tissues and serum. Spermatogenesis was evaluated with the Johnsen scoring system. Results. The testicular tissue and serum levels of MDA, PC, and SOD activity were increased in the obesity group in comparison to the sham operated group (P<0.05). Weight loss and melatonin treatment ameliorated MDA, PC, and SOD levels in testicular tissue and serum significantly (P<0.05). There was no significant difference between groups in terms of mean Johnsen score (P=0.727). Conclusion. Experimentally created obesity caused oxidative stress and both melatonin and weight loss reduced oxidative stress parameters in rat testes.